Answered

Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Join our Q&A platform to connect with experts dedicated to providing precise answers to your questions in different areas. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

let a and b be the roots of the equation x^2 - 3x - 1 = 0. Find a^3 + b^3

hint: a^3 + b^3 = (a+b)(a^2-ab+b^2)

URGENT PLEASE


Sagot :

Answer:

Correct option is A)

Given,a,b are distance roots of x

3

+3x

2

−1=0

⇒a

3

+3a

2

−1=0 and b

3

+3b

2

−1=0

let the third root be c

then c

3

+3c

2

−1=0

product of roots =

a

−d

=

1

−(−1)

=1

abc=1

c=

ab

1

but c is root of x

3

+3x

2

−1=0

⇒c

3

+3x

2

−1=0

(ab)

3

1

+

(ab)

2

3

−1=0

1+3ab−(ab)

3

=0

.....(1)

in equation (1)

(ab)

3

−3(ab)−1=0

⇒ab is root of

x

3

−3x−1=0

∴(ab) is root of

x

3

−3x−1=0